X-Ray Powder-Pattern of Pd(II) Complexes Derived from Various Substituted Schiff Bases - Mehta, B.H.; Vengurlekar, V.P. (Asian Journal of Chemistry, 2010)
This is in continuation with our work on synthesis and characterisation of Pd(II) complexes derived from Schiff bases, which were diagnosed for X-ray spectral data. A powder pattern of each complex was recorded and the data were indexed using least square method. All the compounds were X-ray crystalline. The pyknometric density and the density calculated from X-ray data are in good agreement. The compounds were indexed to monoclinic crystal system with a space group C2/m or P2/m .